Rent: The final performance - filmed live on Broadway - Hicks, Rodney; Kantor, Adam; McElroy, Michael; Warren, Michael John (Sony Pictures Home Ent., 2009)
Live Broadway performance of Jonathan Larson's hit musical Rent. See one of the longest-running Broadway shows from the best seat in the house as it come to the end of its run. The musical follows the ups and downs of a year in the lives of a group of friends living in New York's East Village. This performance also features special appearances from some of the members of the original cast.